Profitability and Market on Stock Returns in Mining Companies on The Indonesia Sharia Stock Index for the 2016 - 2020 Periods - Sucipto Sucipto; Erwin Saputra Siregar; Mariyani Mariyani (Maliki Islamic Economics Journal, 2023)
Returns on stocks are the benefits businesses, individuals, and organizations receive directly from their investment decisions. Every short or long-term investment has one primary goal: to generate a profit, also known as a return. This can happen in either a direct or indirect manner. This study aimed to test and collect empirical data on the impact of ROA, ROE, EPS, and PER on stock returns. Panel data regression was used, and the research data came from each mining firm's annual reports and financial statements included in the Indonesian sharia stock index from 2016 to 2020. So, according to the findings of this study, ROA, ROE, and PER have a significant beneficial impact. Quite large on stock returns because the company's management can manage ROA, ROE, and PER effectively to create high profits, encouraging investors to invest. Meanwhile, EPS does not significantly affect stock returns because companies with low earnings per share do not accurately reflect the profits that investors will get, thus making investors less interested in investing their capital. Simultaneously ROA, ROE, EPS, and PER affect stock returns.